Analisa Aplikasi Supply Chain Management Telkom (SCMT) untuk Pendataan Pengeluaran & Pengembalian Barang NTE PT. Telkom Datel Sibolga - Putri Khairani Pratiwi; Annio Indah Lestari Nasution; Rizka Azriani Tanjung (Pusat Riset dan Inovasi Nasional, 2024)
The internship was carried out at PT Telkom Datel Sibolga, Pasar Baru Village, Sibolga Kota District, North Sumatra Province on January 16 - February 17, 2023. The purpose of this Internship activity is to find out how the application of the Telkom Supply Chain Management website on the recap of expenditure / return of goods of PT Telkom Datel Sibolga. PT Telkom Datel Sibolga is a company engaged in telecommunications with a large working area so far the inventory maintenance process is still carried out manually, so the results are not fast and inaccurate, in addition to the time required longer this process becomes ineffective and efficient. Therefore, it is necessary to implement the Telkom Supply Chain Management (SCMT) application that supports the flow of an item both by application and manually. In collecting research data, quantitative methods are used which consist of observations and interviews, then problem analysis is carried out using a framework of pieces and use case diagrams. The results obtained from the internship activities are that in the first week to the end of the study it was found that the expenditure of Optical Network Termination (ONT) goods was more than the Set Top Box (STB) an Telkom Supply Chain Management (SCMT) process until the end carried out by PT Telkom Indonesia at STO Sibolga has been running in accordance with the SCMT application.